Rozwiąż równania
a)3(x+3)=2(x+4)+x+1
b)4(3x+2)+5(2x+3)=-(2x+13)
c)4(x-2)-2(x-4)=5(x+1)-3x
d)x+3
¯¯ -(1-x)=3,5
2
e)1 2 3 1 2 1
¯ (y-3)- ¯ (y- ¯ )+ ¯ = ¯ - ¯(2y-3)
5 3 5 3 5 3
f)2x+4 1
¯¯¯¯¯ = ¯x+1
4 2

g)4-5 2y+3 1 y+7 y
¯¯¯ + ¯¯¯¯+ ¯= ¯¯¯+¯
2 5 3 15 2
h)y 1 7
¯+¯ = ¯
2 3 6
i)-0,07(10x-1)=0,3x
j)0,6x+2(0,1x-0,1)=0,2(x+1)

1

Odpowiedzi

2010-03-24T20:45:43+01:00
1
a)3x+9=2x+8+x+1
3x+9=3x+9
0=0
b)12x+8+10x+15=-2x-13
22x+23=-2x-13
24x+23=-13
24x=36
x=6/9

c)4x-8-2x+8=5x+5-3x
2x=2x+5
0=5
sprzecznie
d)x+3-1+x=7
2x+2=7
2x=5
x=5/2

e,F,G,H nie umiem rozczytać co tam napisane

i)-0,07(10x-1)=0,3x
0,7x+0,07=o,3x
0,4x=0,07
x=0,175

j)0,6x+0,2x-0,2=0,2x+0,2
0,8x=0,2x
też sprzeczne